2014
DOI: 10.1093/fampra/cmu053
|View full text |Cite
|
Sign up to set email alerts
|

Organizational aspects of primary care related to avoidable hospitalization: a systematic review

Abstract: Available evidence suggests that strong primary care in terms of adequate primary care physician supply and long-term relationships between primary care physicians and patients reduces hospitalizations for chronic ACSCs. There is a lack of evidence for the positive effects of many other organizational primary care aspects, such as specific disease management programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
119
1
19

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(145 citation statements)
references
References 61 publications
6
119
1
19
Order By: Relevance
“…The results were consistent with previous research that has found that both primary care resourcing and deprivation levels have an effect on admissions to hospital for both diabetes complications and COPD [4][5][6]. This study extends those results by showing how these factors can also interact with complex structures of entitlements, where greater eligibility for free care can reduce the negative effects associated with deprivation, but with potentially higher levels of avoidable hospitalisation in areas with both low levels of resourcing and eligibility for free care.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results were consistent with previous research that has found that both primary care resourcing and deprivation levels have an effect on admissions to hospital for both diabetes complications and COPD [4][5][6]. This study extends those results by showing how these factors can also interact with complex structures of entitlements, where greater eligibility for free care can reduce the negative effects associated with deprivation, but with potentially higher levels of avoidable hospitalisation in areas with both low levels of resourcing and eligibility for free care.…”
Section: Discussionsupporting
confidence: 92%
“…However, any effort to reduce admissions in areas with high rates requires analysis of the reasons for the variation in rates in the first place. Rates of hospitalisation for ambulatory-care sensitive conditions have been linked to primary care resourcing, including the number of general practitioners per population [4,5], and to characteristics of the population, such as deprivation [6].…”
Section: Introductionmentioning
confidence: 99%
“…Our results suggest that seeing the same family physician over time can improve the physical health of people with SMI and thereby reduce their need for and use of unplanned hospital care. These findings are consistent with previous studies that found relational continuity to be associated with reduced risk of ACSC admission in a range of different patient groups . Higher continuity of family physician care may reduce the need for hospital care through improved management of physical health, by facilitating familiarity, communication, trust, and quality of relationship between doctor and patient .…”
Section: Discussionsupporting
confidence: 91%
“…This is one of the most ambulatory common care-sensitive conditions and one of the most prevalent chronic diseases among children (26) , and should be identified and treated through primary healthcare (1) . A literature review suggested four important aspects for the effective management of chronic disease and subsequent prevention of admissions due to these conditions: the prevention services offered by the local health system, good access, adequate facilities, and organisation of the care process (27) .…”
Section: Discussionmentioning
confidence: 99%